Proximate Composition of Seeds of Some Lesser-Known Crops - R. A., Oloyo; N. O. A., Ilelaboye (Universiti Putra Malaysia Press, 2002)
Seeds of Jatropha curcas, Trichosanthes cucumerina, Annona muricata and Citrullus vulgaris were analysed for proximate composition, cell wall carbohydrates, nutritive and non-nutritive components and then their energy values were estimated. Crop seeds contained per kg: 113.1 - 324.5 g crude protein, 364.8 - 483.3 g fat, 29.3 - 296.8 g crude fibre, 29.8 - 37.8 g total ash, 111.9 - 222.8 g soluble carbohydrate, 41. 0 - 363.4 g cell wall carbohydrate, 18.0- 169.0 g cellulose, 23.9- 194.4 g hemicelluloses, 706.5 - 970.7 g cellular matter, 685.3 - 947.0 g organic cellular matter, 10.4 - 29.6 g soluble ash, 5.2 - 19.4 g acid-insoluble ash, 25.5 39.4 g non-nutritive matter, 20.0 - 48.6 g lignin, 19.2 - 25.6 MJ total energy, 9.0 - 21.9 MJ digestible energy and 66.5 - 269.4 g digestible crude protein. It was concluded that except for Annona muricata, all the seed samples are potentially good sources ofdietary energy and protein supplements for ruminants. The need to further investigate the inorganic matter for their mineral element constituents in order to ascertain adequacy or otherwise in meeting the animal requirement is suggested.